CALOTROPIS GIGANTEA, A PROMISING FEED ADDITIVE IN THE NUTRITION OF ORNAMENTAL FISH, KOI CARP (CYPRINUS CARPIO VAR. KOI). - SREEJA, R.S.; MANJU, K.G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
A feeding trial was conducted to evaluate the effect of Calotropis gigantea incorporated diet on the growth performance and protein content of Ornamental fish, Koi carp (Cyprinus carpio var. koi) fingerlings. 60 fingerlings were equally distributed in to six experimental troughs. Test feed (D2) was prepared by replacing 25% of fishmeal with C. gigantea leaf powder and one control feed (D1) without plant powder. Fish were fed (a) of 5% of their wet body weight twice a day at 12 hours interval for 8 weeks. Fish growth parameters (length and weight) were taken every 15 days. The data were statistically analyzed using student's t-test. Results showed that, most of the growth parameters assessed showed significantly better values (p<0.05) in fish fed with D2 when compared with D1. The study indicated that, the C. gigantea incorporated feed can be used by replacing fishmeal still their efficacy need to be improved in future at farm level.